Effect of Surface-Etching Treatment, Glaze, and the Antagonist on Roughness of a Hybrid Ceramic after Two-Body Wear - Grangeiro, Manassés Tercio Vieira [UNESP] (2022)
Stains and glaze are effective procedures for achieving an aesthetic smoothness on indirect restorations. Thus, the effect of surface-etching treatments previous to the stain layer and the glaze application on the occlusal and antagonist wear of a hybrid ceramic were evaluated against different antagonists. Disc-shaped samples were prepared from polymer-infiltrated ceramic network (PICN) blocks. The specimens were divided into eight groups, according to the surface-etching treatment and glaze application: P (polished specimens); PG (polishing plus glaze); E (hydrofluoric acid etching plus stain); EG (acid etching plus stain plus glaze); A (aluminum oxide sandblasting plus stain); AG (sandblasting plus stain plus glaze); S (self-etching primer plus stain); SG (self-etching primer plus stain plus glaze). Half of the samples were subjected to a wear simulation with a steatite antagonist, and the other half was tested using a PICN antagonist. The test parameters were: 15 N, 1.7 Hz, 6 mm of horizontal sliding, 5000 cycles. The discs and the antagonists’ masses were measured before and after the wear tests. The average roughness and spacing defects were evaluated. The etching treatment affected the surface and antagonist mass loss when tested against steatite. AG showed the highest mass loss. This influence was not detected when using the PICN antagonist. The glaze application after staining ensures a smoother surface and avoids antagonist wear.